Making safeguarding personal: learning and messages from the 2013/14 programme. Issue 3 (8th June 2015) - Cooper, Adi; Lawson, Jane; Lewis, Sue; Williams, Cathie
Abstract : Purpose: – The purpose of this paper is to describe the Making Safeguarding Personal (MSP) programme undertaken in 2013/2014 and summarises the learning and messages from this phase of work. This informed both the subsequent mainstreaming of the programme to all councils, and national policy on safeguarding adults in England. Design/methodology/approach: – Following the "test bed" phase in 2012/2013, MSP pilots were developed in 53 councils. They adopted a new outcomes focused and person led approach to adult safeguarding practice. Supported by the Local Government Association and partners, these councils changed their safeguarding practice and how adults were involved in safeguarding processes. Adults' wishes were identified at the early stages of investigation, and reviewed during and at the end of the safeguarding process. In total, 43 councils provided impact statements on work undertaken, mainly between December 2013 and February 2014. Findings: – Key findings from the impact statements evidenced that adopting a personalised approach made safeguarding more effective and provided opportunities for developing social work practice. A range of challenges were encountered and overcome. The experiences of the MSP pilot sites informed the Care Act guidance issued in October 2014. Originality/value: – The MSP programme has stimulated an innovative culture change in safeguarding adults' practice. It provides a means for Safeguarding Adults Boards to ascertain the effectiveness of local services in achieving the desired outcomes of vulnerable adults at risk of abuse or harm. Practitioners, managers and others will have an interest in this major change.